Launch of the Human Development Report 1994 in Copenhagen (UNDP New YorkUS, 1994)
Presents Dr. Mahbub ul Haq's speech delivered at the launch and the address given by Helle Degn, Minister for Development Cooperation of the Government of Denmark.
Speeches from the launch sponsored by the Danish Government and UNDP